2018
DOI: 10.1007/s11764-018-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of a web-based app to improve breast cancer symptom management and adherence for aromatase inhibitors: a randomized controlled feasibility trial

Abstract: If short-term gains in adherence persist, this low-cost intervention could improve survival outcomes for women with breast cancer. A larger, long-term study should examine if AI adherence and symptom burden improvements persist for a 5-year treatment period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
126
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 50 publications
9
126
0
2
Order By: Relevance
“…Geographically, one paper reported sampling from 18 countries across the world, heavily sampling from Europe, but also including Australia, and four countries from South America. Other studies sampled more culturally discrete regions, eg, China ( k = 1), Germany ( k = 3), and the United States ( k = 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographically, one paper reported sampling from 18 countries across the world, heavily sampling from Europe, but also including Australia, and four countries from South America. Other studies sampled more culturally discrete regions, eg, China ( k = 1), Germany ( k = 3), and the United States ( k = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most ( k = 7) interventions used a control group comparison, while one employed a single group design. Studies reported data at 2 years, at 1 year, and shorter‐term follow‐up data collection . The definition of adherence was largely uniform across studies with most ( k = 6) defining adherent as ≥80% of scheduled doses.…”
Section: Resultsmentioning
confidence: 99%
“…Related studies have been carried out [13][14][15]. However such studies have some deficiencies such as a singular method of exercise intervention and exercise guidance [16][17][18][19]. Therefore, due to the limitations of previous studies, we aimed to investigate the effects of the CEIBISMS on QOL, muscle strength and cardiorespiratory capacity in postoperative BC patients in China.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud calculating suggests resilient distribution ways among health environments to health care workers (59). Peer support is an essential component of the behavioral change programs, which lets consumers share their awareness, beliefs, attitudes, experiences, emotional, social, or applied for support with each other (30).…”
Section: Resultsmentioning
confidence: 99%
“…Several mobile-based delivery templates were detected in 11 chosen articles; these templates include mobile app-based (34,35,37), web-based (56)(57)(58)(59), the internet, email (60,61), short text message (62), and computers (63). Self-care, a healthy lifestyle, and stress management are essential elements in developing healthy lifestyle interventional programs (57).…”
Section: Methodsmentioning
confidence: 99%